2014
DOI: 10.1007/s00192-014-2525-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of body mass index on the biomechanical properties of the human prolapsed anterior vaginal wall

Abstract: Contrary to our hypothesis, this study observed a relationship between BMI and human AVW biomechanical properties, with more obese women having stiffer tissue properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…The clinical literature does not report much on the biomechanical properties of the vagina of asymptomatic women over the course of their life. The available data demonstrate that women with a high BMI or who are menopausal have a stiffer vaginal wall [31,32]. In our menopausal sheep, we also observed an increase in stiffness.…”
Section: Discussionsupporting
confidence: 68%
“…The clinical literature does not report much on the biomechanical properties of the vagina of asymptomatic women over the course of their life. The available data demonstrate that women with a high BMI or who are menopausal have a stiffer vaginal wall [31,32]. In our menopausal sheep, we also observed an increase in stiffness.…”
Section: Discussionsupporting
confidence: 68%
“…Both old and young vaginal tissues exhibited nonlinear stress-strain relations and Mullin's effects [76,77]. Typically, with age comes weight gain, and a recent study conducted by Lopez et al [79] showed that the stiffness of prolapsed vaginal tissue increased with increasing body mass index. Given the strong correlation between parity and pelvic organ prolapse development, the impact of parity on the mechanical properties of the vagina was recently investigated by Knight et al [80] in the ewes.…”
Section: Testing Methods and Materials Propertiesmentioning
confidence: 99%
“… A : Stress versus strain plot for freshly excised HAVW measured in uniaxial tension (no cycling) Zimmern et al B : Uniaxial tension with recycling Lopez‐Ochoa et al…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The peak stress level can be chosen to approximate that experienced during a physiological maneuver, for example, coughing, Valsalva; in addition, a “rest” interval can be employed. Typical results are shown in Figure B, taken from Lopez‐Ochoa et al…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation